Factors affecting conversion of laparoscopic to open cholecystectomy - Chhetri, Raj Kumar; Shrestha, Muza; Shrestha, Ram Prasad (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Laparoscopic cholecystectomy is the gold-standard operation for the treatment of cholelithiasis. Various factors affect the conversion of laparoscopic to open cholecystectomy. Methods: In this prospective analytical study one hundred and sixty consecutive patients who underwent laparoscopic cholecystectomy were studied to see the factors that affect the conversion to open cholecystectomy. Factors contributing to conversion of laparoscopic to open cholecystectomy were analyzed. Result: In this study the conversion rate of laparoscopic to open cholecystectomy was 6.25%. The most common cause for conversion was unclear anatomy and adhesion at the Calot’s triangle and abnormal course of the cystic artery. Conclusion: Proper knowledge about the anatomical variations of cystic duct and artery and timely conversion in cases of confusion can help prevent bile duct injuries during cholecystectomy.